2019
DOI: 10.2217/imt-2018-0208
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of Combination Immunotherapy And Targeted Therapy in the Treatment of BRAF -mutant Advanced Melanoma: A Matching-Adjusted Indirect Comparison

Abstract: § M Rael was an employee of Evidera, Inc. at the time of study and manuscript development Aim: Comparison of clinical outcomes of nivolumab + ipilimumab versus BRAF + MEK inhibitors (dabrafenib + trametinib or vemurafenib + cobimetinib) in BRAF-mutant advanced melanoma. Methods: Matching-adjusted indirect comparisons were conducted between nivolumab + ipilimumab (Check-Mate 067/069 studies) and BRAF + MEK inhibitors (COMBI-d, COMBI-v and coBRIM studies). Overall survival (OS), progression-free survival and obj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
0
32
0
Order By: Relevance
“…For example, in a recent matching-adjusted indirect comparison, clinical outcomes with nivolumab plus ipilimumab were compared with dabrafenib plus trametinib or vemurafenib plus cobimetinib combination treatments in patients with BRAF-mutant advanced melanoma. 47 After adjusting for differences in baseline characteristics, PFS and response outcomes were similar among the treatments; but, beyond 12 months of treatment, nivolumab plus ipilimumab improved OS compared with targeted therapy. This suggests that the survival benefit with combination immunotherapy emerges later and may be more durable than with targeted therapies.…”
Section: Discussionmentioning
confidence: 88%
“…For example, in a recent matching-adjusted indirect comparison, clinical outcomes with nivolumab plus ipilimumab were compared with dabrafenib plus trametinib or vemurafenib plus cobimetinib combination treatments in patients with BRAF-mutant advanced melanoma. 47 After adjusting for differences in baseline characteristics, PFS and response outcomes were similar among the treatments; but, beyond 12 months of treatment, nivolumab plus ipilimumab improved OS compared with targeted therapy. This suggests that the survival benefit with combination immunotherapy emerges later and may be more durable than with targeted therapies.…”
Section: Discussionmentioning
confidence: 88%
“…Current treatment options for unresectable stage III and stage IV disease (5) include BRAF-targeted therapies for patients that have BRAF-mutant melanomas, and ICIs with anti-PD-1 alone or in combination with anti-CTLA-4. However, durable response is only seen in a minority of patients, and the optimal sequencing of therapies and the selection of the most effective first-line therapy, remain controversial (6,7). The CheckMate 067 trial demonstrated that the combination ipilimumab and nivolumab resulted in superior long-term survival outcomes compared with either nivolumab or ipilimumab monotherapy, with a 5-year overall survival of 52% (8).…”
Section: Introductionmentioning
confidence: 99%
“…Considering an additional subgroup analysis from CheckMate 067 showing a 64% survival rate in all patients with normal baseline LDH and less than three organ sites with metastases, it is likely that combined ICB might show a 5-year survival rate > 64% in BRAF -mutated patients showing additional favorable baseline characteristics. Although these results should be interpreted with great caution, an indirect comparison by Atkins et al showed improved survival outcome in BRAF -mutated melanoma patients receiving ipilimumab plus nivolumab compared with V + C and D + T [ 52 ]. This is also supported by indirectly comparing the 5-year landmark OS rates of COMBI-v/d and CheckMate 067 (34% vs. 60%).…”
Section: Summary/discussionmentioning
confidence: 99%